2021
DOI: 10.1080/10717544.2021.1934189
|View full text |Cite
|
Sign up to set email alerts
|

An efficient enzyme-triggered controlled release system for colon-targeted oral delivery to combat dextran sodium sulfate (DSS)-induced colitis in mice

Abstract: Oral route colon-targeted drug delivery systems (CDDSs) are desirable for the treatment of ulcerative colitis (UC). However, CDDSs are challenging owing to the physiological and anatomical barriers associated with the gastrointestinal tract (GIT). In this study, we developed an effective enzyme-triggered controlled release system using curcumin–cyclodextrin (CD–Cur) inclusion complex as core and low molecular weight chitosan and unsaturated alginate resulting nanoparticles (CANPs) as shell. The formed CD–Cur–C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…In the digestive tract, the patient's mucosa was correspondingly damaged, and the ability to absorb nutrients was significantly reduced [ 20 ]. The body's vitamin D level was significantly deficient, and the risk of diffuse muscle pain in the waist, pelvis, and lower limbs was significantly increased [ 21 ]. It had been confirmed in foreign studies [ 22 24 ] that the level of 25 hydroxyvitamin D showed a significant correlation with the dosage of opioids in tumor patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the digestive tract, the patient's mucosa was correspondingly damaged, and the ability to absorb nutrients was significantly reduced [ 20 ]. The body's vitamin D level was significantly deficient, and the risk of diffuse muscle pain in the waist, pelvis, and lower limbs was significantly increased [ 21 ]. It had been confirmed in foreign studies [ 22 24 ] that the level of 25 hydroxyvitamin D showed a significant correlation with the dosage of opioids in tumor patients.…”
Section: Discussionmentioning
confidence: 99%
“…The integrity of the gut epithelial barrier is compromised in UC patients, including decreased expression of tight junction proteins (ZO-1, occludin and claudin-1), increased intestinal mucosal permeability and impaired intestinal mucosal tissue. [21][22][23][24] Meanwhile, the composition of the gut microbiota in UC patients changes significantly, resulting in more flagellin and lipopolysaccharide (LPS) in the gut microbiota, promoting the expression of pro-inflammatory factors and causing intestinal inflammation. In addition, bacteria are more likely to invade the dense mucus layer, making it easier for harmful bacteria to contact intestinal mucosal cells, so as to stimulate the production of proinflammatory cytokines and then recruit immune cells.…”
Section: Pathological Changes Of Uc and Its Management Strategiesmentioning
confidence: 99%
“…In our previous study, an effective enzyme-triggered controlled release system using a curcumin-cyclodextrin (CD-Cur) inclusion as the core and CANPs as the shell (Li et al., 2021 ). This specific colon-targeted drug delivery system showed significant pH-dependent properties, protecting the drugs through GIT.…”
Section: Application Of Canps In Colitis Therapymentioning
confidence: 99%